Neutrino Oscillation Probabilities and the Enigma of Sterile Neutrinos: A Review - Sharma, Preet (Current Research Progress in Physical Science Vol. 7, 2025)
Neutrino oscillation is a quantum mechanical phenomenon whereby a neutrino created with a specific lepton flavour (electron, muon, or tau) can later be measured to have a different flavour. In the past decades, there have been many groundbreaking discoveries and advancements in the field of particle physics. One of the important elementary breakthroughs is the phenomenology of neutrino oscillations. This includes the properties of neutrinos in the Standard Model (SM) and how neutrino oscillations and their properties have been so important in strengthening the SM. In the Standard Model (SM), neutrinos are electrically neutral and massless. Neutrino oscillations also play a vital role in understanding the current nature of our Universe and the way it behaves. There is also a great interest in neutrino oscillations and their connection with dark matter. This review started with an introduction and discussion of the theoretical background of neutrino oscillations and some experiments, which are working to detect the properties of neutrinos. Then the fundamentals of neutrino oscillations and their interactions were described. Since there are multiple sources of neutrinos, the three sectors were described through which neutrinos can be produced. These are the atmospheric, solar, and reactor sectors. A brief section on the important milestones in neutrino oscillations was included because of the experiments and what they use to detect neutrino properties. Finally, a section on sterile neutrinos was also included since they have been under study for a long time and there is a possibility of them being connected to dark matter interactions. The future work is related to focusing on the current phenomenology of neutrinos and their connection to dark matter. There are various scenarios that have promising aspects of dark matter detection and multiple ways of understanding neutrino oscillations and dark matter.